PERTUMBUHAN ISOLAT Phytophthora infestans (Mont.) de Bary TANAMAN KENTANG DAN TOMAT PADA BERBEDA MEDIA DI LABORATORIUM - Sri Ahdani Yuta; Mukhtar Iskandar Pinem; Lahmuddin Lubis (Universitas Sumatera Utara, 2013)
The growth of Phytophthora infestans (Mont.) de Bary isolate of potato and tomato ondifferent media at Laboratory. This Research was to study the growth of P. infestans on differentmedia at Laboratory. This research was done in Laboratory of Plant disease, AgroecotechnologyProgram Study, Faculty of Agriculture, University of Sumatera Utara, Medan from July toDecember 2012. The method of This research was Completely Randomized Design Factorial withtwelve combinations and two replications. The results showed that the easiest growth isolate ofP. infestans on media was founded potato tubers (I2). The Best growth media of P. infestans wasfounded on media TEA (M3). The fastest growth and diameter of P. infestans was founded inpotato tubers on media TEA (I2M3) and slowest in the potato tubers isolates on PDA (I2M1).Macroscopic and microscopic morphology all isolates are completely same.Keywords: Phytophthora infestans, media, morphology.